Analytical Solution to the Generalized Complex Duffing Equation. - Salas S., Alvaro H. (2022)
Future scientifc and technological evolution in many areas of applied mathematics and modern physics will necessarily depend on dealing with complex systems. Such systems are complex in both their composition and behavior, namely, dealing with complex dynamical systems using diferent types of Dufng equations, such as real Dufng equations and complex Dufng equations. In this paper, we derive an analytical solution to a complex Dufng equation. We extend the Krylov–Bogoli´ubov–Mitropolsky method for solving a coupled system of nonlinear oscillators and apply it to solve a generalized form of a complex Dufng equation.